2014
DOI: 10.1177/1556264614552627
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of an Electronic Informed Consent Process

Abstract: A pilot study assessed an electronic informed consent model within a randomized controlled trial (RCT). Participants who were recruited for the parent RCT project were randomly selected and randomized to either an electronic consent group (n = 32) or a simplified paper-based consent group (n = 30). Results from the electronic consent group reported significantly higher understanding of the purpose of the study, alternatives to participation, and who to contact if they had questions or concerns about the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 22 publications
(27 reference statements)
1
73
0
2
Order By: Relevance
“…Without medical or legal expertise, patients have been chronically misinformed as to the purpose, risks, benefits and procedures described on consent forms 5 . Most consent documents are worded for individuals with post-high school reading levels and are written in complex legal language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without medical or legal expertise, patients have been chronically misinformed as to the purpose, risks, benefits and procedures described on consent forms 5 . Most consent documents are worded for individuals with post-high school reading levels and are written in complex legal language.…”
Section: Introductionmentioning
confidence: 99%
“…A user-centered design approach 7 was selected to facilitate comprehension of the risks and benefits of consenting to HIE using interactive tools to improve decision making ability 5 . Findings from phase one of this study published elsewhere 8 suggested that there was: (1) limited understanding about HIE, (2) an inability to distinguish HIE from the Health Insurance Portability and Accountability Act (HIPAA) 9 , and (3) fragmented clinical workflow that prevented HIE consent from being discussed and obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The study compared a simplified paper consent form only to a video plus the simplified paper consent form. The results demonstrated improved comprehension on some aspects of study specific details [33]. This intervention will be tested in the State of Michigan and the Michigan BioTrust on participant comprehension and uptake (NIH R01 HD082148-01A1).…”
Section: Education and Consent Approachesmentioning
confidence: 99%
“…Although there is little published evidence of this, it is our own local experience and that of other groups involving resource patients/parents. Information and consent for clinical research have often been reduced to the signing of a paper form, but the power of modern information technology is such that a web page, or an interactive web site, a video presentation, or other methods might well be more effective, and might well lead to better informed parents, and more representative samples being recruited [31, 32]. Parents may well prefer being met as a group, as opposed to the one-on-one traditional meeting with a member of the research team.…”
Section: Historymentioning
confidence: 99%
“…Parents may well prefer being met as a group, as opposed to the one-on-one traditional meeting with a member of the research team. The Seattle group have produced a series of videos that address issues around informed consent and randomization, which can be used to teach participants and parents about the meaning of many technical terms that are used [32]. Parents of babies in the NICU are also usually younger than the clinical researchers and are often more “tech-savvy” and may be more likely to interact with web-based methods of information and consent.…”
Section: Historymentioning
confidence: 99%